2022
DOI: 10.33423/jhetp.v22i5.5217
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Blended Instructional Approach in Improving Students’ Scientific Learning Outcomes: A Meta-Analysis

Abstract: This study examined the effectiveness of blended instructional approach in improving students' scientific learning outcomes. This study employed a quantitative research design, where meta-analysis guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol was mainly used to determine the effectiveness of previously done studies on blended instructional approaches. Using Comprehensive Meta-Analysis (CMA) software, the study extracted 53 effect sizes from 49 empirical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…On the other hand, we find that most instructional strategy predictors have little effect on mean science achievement, with the exception of students work in the same ability group . This contradicts earlier reports that claim that teaching approaches play an important role in academic attainment (Antonio, 2022; Ganyaupfu, 2013; Okam & Zakari, 2017; Shana & Abulibdeh, 2020; Tang et al, 2022).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, we find that most instructional strategy predictors have little effect on mean science achievement, with the exception of students work in the same ability group . This contradicts earlier reports that claim that teaching approaches play an important role in academic attainment (Antonio, 2022; Ganyaupfu, 2013; Okam & Zakari, 2017; Shana & Abulibdeh, 2020; Tang et al, 2022).…”
Section: Discussioncontrasting
confidence: 68%
“…In a comparative study of the impact of traditional, inquiry‐based, and research‐based laboratory curricula on the understanding of the nature of science, Russell and Weaver (2011) found that research‐based laboratory curriculum was the most effective compared to the traditional, and inquiry‐based curricula. Antonio's study (2022) indicated that blended teaching approaches have significant positive effect on science achievement. Blended instruction integrates the approaches of face‐to‐face classroom instruction and online learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Correspondingly, a blended learning environment is by nature heavily dependent on the use of technology. Therefore, it is vital that teachers can understand and use different technologies effectively and meaningfully because the competent use and integration of technology positively affects students' learning and achievement (Antonio, 2022). This can include learning how to use the tools and features of new digital platforms in an effective way or how to https://doi.org/10.21428/8c225f6e.768acd6b exploit big data to evaluate students' progress.…”
Section: Pedagogical and Technological Skillsmentioning
confidence: 99%
“…This supports the findings of Heilporn et al (2022) who show that having effective instructional strategies within a blended learning environment creates clarity and better engagement for students. Although we did not interview students, we hope that as we continue to develop our competent use of the digital platform and seamlessly integrate the online and face-to-face elements of the course, we can help facilitate better student learning (Antonio, 2022). Some of the journal entries tell stories about how the architectural constraints of the platform prevented us from enacting our previous teaching practices, but that we found ways to circumvent these by being pedagogically innovative.…”
Section: Which Teacher Competencies Are Perceived Asmentioning
confidence: 99%
“…In light of the changing educational landscape caused by the COVID-19 pandemic, science teachers must become knowledgeable of the effective blended learning strategies that have been investigated and implemented to guide and support them in their instructional practices (Antonio, 2022). Particularly, innovative and effective instructional strategies in Physics are necessary to assist students in developing their learning achievement amidst the online distance learning setup.…”
mentioning
confidence: 99%